Atypical presentation of posterior reversible encephalopathy syndrome: a case report - Nagasuri, Sri Sushma; Konin, Savita; Devarmani, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Posterior reversible encephalopathy syndrome (PRES) is a reversible syndrome characterized by seizures, headache, altered mentation, and loss of vision associated with white matter changes on imaging. A 25-year-old primigravida presented at 31 weeks gestation with atypical PRES characterized by generalized seizures and altered mental status. Magnetic resonance brain imaging showed high-intensity lesions in bilateral corona radiata, capsulo-ganglionic region, genu and splenium of corpus callosum, cortical and subcortical white matter of bilateral high fronto-parietal, bilateral cerebral peduncle, pons and medulla. Cases of antepartum atypical PRES are rare. Patients with atypical PRES do not always show typical manifestations. Our case reports highlight the crucial role of a prompt diagnosis, the importance of rapid blood pressure reduction, with a multidisciplinary approach.